2019
DOI: 10.1002/jeab.554
|View full text |Cite
|
Sign up to set email alerts
|

A cluster analysis of text message users based on their demand for text messaging: A behavioral economic approach

Abstract: The goal of this study was to determine whether cluster analysis could be used to identify distinct subgroups of text message users based on behavioral economic indices of demand for text messaging. Cluster analysis is an analytic technique that attempts to categorize cases based on similarities across selected variables. Participants completed a questionnaire about mobile phone usage and a hypothetical texting demand task in which they indicated their likelihood of paying an extra charge to continue to send t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Consistent with previous studies using the measure of likelihood of purchase to quantify demand for commodities (e.g., Roma et al, 2016), previous research has also documented that greater demand for social reinforcers is associated with various forms of problematic mobile phone use such as texting while driving (Hayashi, Friedel, et al, 2019a, 2019b), text-message dependency (Hayashi, Friedel, et al, 2019b;Hayashi & Blessington, 2021), inclass media multitasking (Hayashi, Friedel, et al, 2019b;Toyama & Hayashi, 2023a), and texting while walking (Hayashi, Friedel, et al, 2019b). Additionally, with respect to demand for general Internet/smartphone access (which can include various nonsocial activities, such as online gaming and gambling), previous studies have shown that greater demand is associated with problematic mobile phone use (Acuff et al, 2022) and higher frequency of text messaging (O'Donnell & Epstein, 2019).…”
Section: Previous Researchsupporting
confidence: 80%
“…Consistent with previous studies using the measure of likelihood of purchase to quantify demand for commodities (e.g., Roma et al, 2016), previous research has also documented that greater demand for social reinforcers is associated with various forms of problematic mobile phone use such as texting while driving (Hayashi, Friedel, et al, 2019a, 2019b), text-message dependency (Hayashi, Friedel, et al, 2019b;Hayashi & Blessington, 2021), inclass media multitasking (Hayashi, Friedel, et al, 2019b;Toyama & Hayashi, 2023a), and texting while walking (Hayashi, Friedel, et al, 2019b). Additionally, with respect to demand for general Internet/smartphone access (which can include various nonsocial activities, such as online gaming and gambling), previous studies have shown that greater demand is associated with problematic mobile phone use (Acuff et al, 2022) and higher frequency of text messaging (O'Donnell & Epstein, 2019).…”
Section: Previous Researchsupporting
confidence: 80%
“…One hundred forty-one participants who agreed to participate in this study as a part of informed consent completed the second survey hosted on Qualtrics (Provo, Utah) and were given a code to enter in Amazon Mechanical Turk to receive $2.50. The sample size was determined based on similar previous studies (e.g., Hayashi et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…While acknowledging that the STDS has been validated as a multidimensional scale and using its 3-factor structure when evaluating factorial structure and convergent validity, in order to facilitate comparisons to previous studies Hayashi & Washio, 2020;Hayashi et al, 2019) we opted to explore the distribution of the sociodemographic variables among different levels of PTM based on the tertiles of participants STDS final score: (i) lower tertile; (ii) middle tertile; and (iii) upper tertile. This procedure is in line with previous studies (Andrade et al, 2020) and demonstrated the most prominent effect size between groups, indicating a robust difference in selfperception of PTM (F (2) = 3,570.49, η 2 = 0.813).…”
Section: Problematic Text Messaging (Ptm)mentioning
confidence: 99%